Transcriptomic and metabolomic analyses to study the key role by which Ralstonia insidiosa induces Listeria monocytogenes to form suspended aggregates - Zuo, Xifeng; Chen, Meilin; Zhang, Xinshuai; Guo, Ailing; Cheng, Si; Zhang, Rong (Frontiers in Microbiology, 2023)
Ralstonia insidiosa can survive in a wide range of aqueous environments, including food processing environments, and is harmful to humans. R. insidiosa can induce Listeria monocytogenes to form suspended aggregates, and this process consists of the co-aggregation of two bacteria which allows for more persistent survival and increases the risk of contamination with L. monocytogenes. Different groups of aggregates were analyzed and compared using Illumina RNA sequencing technology, including R. insidiosa under normal and barren nutrient conditions and in the presence or absence of L. monocytogenes, as a way to screen for differentially expressed genes (DEGs) in the process of aggregate formation. In addition, sterile supernatants of R. insidiosa under different nutrient conditions were analyzed using metabolomics to investigate the effect of nutrient-poor conditions on metabolite production by R. insidiosa. Combined analysis of transcriptome and metabolome data to further investigate the induction effect of R. insidiosa on L. monocytogenes in a barren environment. The results of functional annotation analysis on the surface of DEGs and qPCR showed that, under nutrient-poor conditions, acdx, puuE and acs genes of R. insidiosa were significantly up-regulated in biosynthetic processes such as carbon metabolism, metabolic pathways and biosynthesis of secondary metabolites, with Log2FC reaching 4.39, 3.96, and 3.95 respectively, while the Log2FC of cydA, cyoB and rpsJ in oxidative phosphorylation and ribosomal pathways reached 3.74, 3.87 and 4.25. Screening for differential metabolites, 31 key components were identified mainly involving amino acids and their metabolites, enriched to the pathways of biosynthesis of amino acids, phenylalanine metabolism and methionine metabolism, of which aminomalonic acid and Proximicin B are the special components of R. insidiosa metabolized under nutrient-poor conditions.